Estudo etnobotânico de plantas medicinais utilizadas por estudantes indígenas da Comunidade Umariaçu II, Tabatinga, Amazonas - Santos, Igor Tourinho dos (Brasil, 2024)
The medicinal plants used in the comunities date back to the existence of their first residents. Whereas, this knowledge needs to be preserved, thus avoiding the loss of this knowledge acquired from generation to generation. The general objective of this work was to carry out an ethnobotanical study of the medicinal plants used by indigenous students of the Umariaçú II community in the Municipality of Tabatinga, Amazonas. The methodology used in this research was qualitative, as it consists of data collection. The results were obtained from the application of a questionnaire with open questions to the students, focusing on the survey of the medicinal plants used in their homes and observing the appreciation of home medicine. In the results obtained, the use of the leaves for medicinal purposes was highlighted, as (82%) mentioned by the students in the preparation of tea, followed by the stem with (13%), accompanied by fruit (3%) and seed (2%). As for the traditional knowledge mentioned in the research, it prevails that knowledge is passed from generation to generation. As for the use of these plants for the treatment of diseases, they were: digestive system problems (36%) and respiratory system problems (21%), mainly. The species M. officinalis (lemon balm) stood out with 32% of the citations of agreement of use, compared to the other herbs used in the community. The school's students use medicinal plants in their daily lives, demonstrating knowledge about their therapeutic uses, Tea as a source of folk medicine at home. In this way, the role of education is considered important, especially regarding traditional knowledge in indigenous communities, and for this education to be implemented, it is necessary to have public policies aimed at the construction of curricula that effectively enable a differentiated and inclusive education about medicinal plants.